The future of the Pacific under climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Climate change is already hitting the Pacific region which already impacts the region's food system. Recently, a diverse group of policymakers, researchers, farmers and political leaders of the region came together to think about the future of food in the Pacific.